Dental Clinic Interior Model as an Alternative to Child Anxiety - Muhamad Rohim (Syntax Corporation Indonesia, 2021)
Background:. Children experience higher anxiety than adults this is due to emotional differences and mental development according to age, one of the efforts to overcome anxiety is to provide dental health education using methods, media and models of dental clinic rooms tailored to the needs of the child. In general, dental clinic rooms have white and creepy shades. The interior model of the dental clinic is made specifically to address the anxiety of the child at the time of childcare. Research Objective: produce an interior model of dental clinics as an alternative to child anxiety management Method: Research and Development (R&D) method, and model test using quasi-experimental non randomized control group pre-test and post-test design. Sampling techniques with purposive sampling, the study subjects were children who performed treatment at the dental clinic, divided into 2 groups of 20 children each, group 1. intervention of dental clinic interior models with wall wallpapers and acoustic videostimulions and 2. Media posters and dental health counseling as a control group. Data tested with Wilcoxon and Mann-whitney tests. Result: